Enhancing Physical Environment of Child Care Centres in Malaysia Through Legal Analysis - Mutalib, Mashitah Abdul (Southeast Asia Early Childhood Journal, 2022)
The issue of low quality of child care centres which lead to numbers of unwanted injuries and death of children while in care need to be addressed through legal mechanism. In regulating child care centres in Malaysia, there are certain legal requirements that need to be fulfilled by child care operators. One of the requirements that often neglected is the physical environment. This paper examines the question on whether the physical environment feature in legislative framework of Malaysian child care need improvements. This research is done through doctrinal research analysing the relevant legislations and related documents of Malaysia and other jurisdictions. The laws and regulations in Malaysia involving Child Care Centre Act 1984 and Child Care Centre Regulation 2012 are analysed according to the relevant sections and regulations. The practices from other jurisdictions including Australia, Singapore and Canada are analysed for Malaysia to take lesson from. Recommendations are then made for Malaysia to improve its laws and regulations on physical environment in care centres.